Pediatric intramedullary spinal cord tumors: A single center experience. (January 2015) - Kutluk, Tezer; Varan, Ali; Kafalı, Candaş; Hayran, Mutlu; Söylemezoğlu, Figen; Zorlu, Faruk; Aydın, Burça; Yalçın, Bilgehan; Akyüz, Canan; Büyükpamukçu, Münevver
Abstract Aim To evaluate clinical and radiological findings, pathological features and treatment modalities in pediatric patients with intramedullary spinal cord tumors. Patients and methods The medical records of 36 patients with intramedullary spinal tumors were reviewed for clinical, radiological and histopathological data, chemotherapy, radiotherapy, surgical resection, treatment responses, events, and final outcome. Survival analyses were performed. Results The median age was 7.9 years (range: 1–16 years; male/female ratio:1.4). Majority of the tumors were histopathologically diagnosed as astrocytomas (n = 16, 44.4%) and ependymomas (n = 19, 52.8%); whereas one was unclassified glioma. Overall, 94% of the astrocytomas and 84% of the ependymomas were low-grade, only three tumors were high-grade. In one patient with ependymoma, histopathological grade was undetermined. The primary tumor was commonly located in thoracic (47%) and cervical segments (28%). All patients had undergone surgery (gross-total resection, 33%; subtotal resection, 45%; biopsy, 22%). Radiotherapy was administered to 26 patients (72%) and chemotherapy to 15 patients (42%). The 3-, 5- and 10-year overall survival rates were 72%, 63% and 56%, respectively; and event-free survival rates were 43%, 40% and 40%. Survival did not significantly differ with gender, age groups, lag-time, neurologic status, histopathological tumor type, tumor location, extent of resection, treatment, or treatment responses in univariate survival analyses. Survival rates were significantly higher in patients with low-grade tumors and in ependymoma patients with resected tumors. Conclusions Patients with low-grade tumors and those who underwent gross-total tumor resection had better prognosis. Surgery remains the main treatment in intramedullary spinal tumors. The role of radiotherapy and chemotherapy is limited and even controversial in low-grade tumors.